Harnessing Ethiopian floodwaters helps dryland pastoralists – and the approach is scaling up - CGIAR Research Program on Water, Land and Ecosystems (2019)
We have developed the tools to decide what fertilizer application is needed for a specific landscape, soil type, and rainfall conditions targeting maximum yield gain.